Implementasi Model Pembelajaran Projects Based Learning Pada Materi Forward Reverse Berbasis Zelio Untuk Meningkatkan Keaktifan Dan Hasil Belajar Siswa Di SMKN 1 Kramatwatu - Deni Exka Saputra; Aditya Dwi Raja Kamansastra2; Iqbal Maulana; Allkaf Movlexis Adam; Mustofa Abi Hamidn (International Forum of Researchers and Lecturers, 2024)
Education Is A Very Important Aspect In Efforts To Improve The Quality Of Intelligent Human Resources So That They Can Support The Progress Of The Nation And State In The Future. As One Of The National Development Sectors In An Effort To Make The Nation's Life Smarter, The Vision Of Education Is To Create An Education System As A Strong And Authoritative Social Institution To Empower All Indonesian Citizens To Become Quality Human Beings So That They Are Able And Proactive In Responding To The Challenges Of The Ever-Changing Times. Data Source Sampling Was Carried Out Purposively And Snowball, Data Collection Techniques Used Triangulation, Data Analysis Was Inductive/Qualitative, And Qualitative Research Results Emphasized Meaning Rather Than Generalization. The Descriptive Method Is A Method For Assessing The Status Of A Group Of People, Objects, Conditions, Systems Of Thought, Or Events In The Present. This Type Of Research Tries To Explain Certain Social Phenomena. In This Research, It Starts From Designing A Ladder Diagram. An Existing Ladder Diagram Is Then Made Into A Circuit And Given A Load In The Form Of An Electric Motor That Can Be Controlled With Forward/Reverse. 3-Phase Power Source, Power/Three-Phase Mcb, R/S/T Phase, 1-Phase Mcb, Zelio, Forward And Contact Contacts, 3-Phase Motor As Output From Three Phases, Pb Stop, Pb Forward, And Pb Reverse. The Control Circuit Has Three Main Components, Namely The Zelio Sr Block, Contactor Block And Control Panel. The Three Components Are Interconnected And Coordinated By Zelio Sr As A Pc-Based Control Device. The Zelio Sr Used Is The Sr2 B121fu Type Which Has 4 Output Terminals And Has A Working Voltage Of 220v. System Design Testing In The Research Using The Zelio Plc. A. Simulation In Software. The Image Below Is The Initial Display Of The Application. Education Is One Part Of Developing High Quality Education For All Indonesian People Towards Creating A Quality Indonesian People. The Impact Of Education Is Quite Broad In Various Aspects Of Life Starting From The Economic, Social, Political, Technological, Environmental, Cultural, Educational And So On.